O uso da tecnologia da informação no SUAS Vitória: um estudo do Sigafweb - Girelli, Clarice Machado Imperial (2023)
This study aims to analyze the use of Information and Communication Technology (ICT) in the Unified Social Assistance System in the municipality of Vitória, with the objective of understanding its contribution to management and knowledge production through SigafWeb. A bibliographic and documentary research was conducted from 2007 to 2021. The research presents the elements for understanding the structural determinants of the phenomenon of computerization in contemporary capitalism based on its historical determinations, movements, and contradictions. It discusses the computerization of state management in social policies, particularly in the Social Assistance Policy, the role of the State and the phenomenon of using ICTs in the context of productive restructuring and neoliberalism in Brazil as a model of efficiency, productivity, and selectivity. These foundations underpin the analysis of the trajectory of the Information System of the Secretariat of Social Assistance of Vitória and its contribution to the generation of information and knowledge in a process that advances in the struggle to expand social rights for users of the SUAS, rather than control its users and workers, in a purely technocratic view of the use of information technology.